BASELINE ASSESSMENT OF SELF-CARE PRACTICES AND PSYCHOLOGICAL WELL BEING AMONG YOUNG ADULTS WITH TYPE 1 DIABETES IN A WARRIOR CAMP SETTING - Selveindran, Nalini M; Zaini, Azriyanti Anuar; Noor, Noor Shafina Mohd; Noor, Nurain Mohd; Jalaludin, Muhammad Yazid (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Psychological well-being and effective self-care are critical in the management of young adults with Type 1 Diabetes (T1DM). The T1DM Warrior Camp conducted under the MEMS-CD1C initiative is a unique focused camp to empower young adults with T1DM on advocacy and peer leadership. This study aimed to evaluate baseline levels of depression, anxiety and stress in young adults attending a T1DM camp using the Depression Anxiety Stress Scales-21 (DASS-21) and the self-care practices using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire with a follow-up evaluation planned six months post intervention. METHODOLOGY Fourteen young adults with T1DM (aged 18–25) attended a structured 3-day Warrior Camp focused on diabetes education, lifestyle management and peer engagement. Baseline assessment was done using the DASS-21 and SDSCA questionnaire. RESULT Mean haemoglobin A1c and SDSCA score were 9.34 (± SD 2.43)%. Participants showed the highest adherence in blood glucose monitoring (5.93 ± 1.2), while foot care had the lowest adherence (3.1 ± 1.1). Dietary and exercise behaviours showed moderate adherence. The average stress score was 7.9 ± 1.2, corresponding to mild stress. Participants also reported moderate anxiety and mild depression, based on mean subscale scores. CONCLUSION This initial assessment highlights key areas of strength and opportunity in self-care practices among young adults with T1DM. Notably, blood glucose monitoring was a strong domain, whereas foot care requires greater emphasis. These young adults on assessment report mild to moderate symptoms of psychological distress, highlighting the importance of mental health support in this population. Camps may serve as a valuable setting for monitoring and addressing psychosocial needs in young adults with T1DM. The impact of the Warrior Camp intervention on these two critical areas will be reassessed after six months to evaluate long-term changes.